A thematic analysis of online learning experiences among students of a language programme: instructors’ delivery and peer interaction / Ahmad Harith Md Yusuf … [et al.] - Md Yusuf, Ahmad Harith; Maulan, Sumarni; Fang, Jing; Hoo, Jean; Jailani, Adi Idham; Mohamad Ayob, Norazlina (Akademi Pengajian Bahasa, 2021)
The Fully Online Learning Community (FOLC) framework was authored by Van Oostveen (2016) based on a social constructivism theory that proposes all knowledge develops as a result of social interaction. Amid Covid-19 pandemic, students and instructors alike are forced to be a part of this community of which their experiences with ‘social presence’ are crucial to inform curriculum designers the efficacy of online learning curriculum, Thus, this paper aims to look into the online learning experiences among a group of students in a language programme particularly on their social involvement: instructors’ delivery and peer interaction. A six-stage thematic analysis (TA) (Braun & Clark, 2006) was used to code the data derived from 256 respondents of an open-ended questionnaire. A total of 11 recurring themes were found for instructors’ delivery: platform, material, delivery technique, interaction, support, feedback, live session duration, availability, instructors’ characteristics, mode suitability and materials accessibility. However, only six themes were coded for peer interaction: activities, support, mode suitability, platform, cooperation and the Internet connectivity. These themes correspond with seven of the nine dimensions of online learning design proposed by Means, Bakia and Murphy (2014) which are modality, pacing, instructor role online, student role online, online communication synchrony, pedagogy and source of feedback. In conclusion, TA is useful for curriculum designers and instructors to improve the existing online learning curriculum and practices while it benefits students to make them become better learners in online learning.